HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN LARI 40 METER TERHADAP HASIL LOMPAT JANGKIT PADA ATLET PUTRA PPLP ATLETIK RIAU - Rizki Pernanda; Drs.Saripin, M.Kes, AIFO '; Ni Putu Nita Wijayanti, S,Pd, M,Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research puts its main concern on the difficulty that the athletes face in obtaining the target of the jump, which is 9,97 meter. The research is aimed to discover whether there is any relation between muscular leg power and 40 meter running speed with the result of triple jumping on male athletes PPLP Atletik Riau. The method of sample taking is implementing the total sampling of male athletes PPLP Atletik Riau, the sample in this research is as many as 6 male athletes. Correlation technique is used in the data analysis. Therefore, the data is examined by using normality test—the test in product-moment correlation research—test significant α = 0,05. Normality test variable X1, L0 max (0,1866) < Ltable (0,319), variable X2, L0 max (0,1230) < Ltable (0,319) and normality test variable Y, L0 max (0,2088) < Ltable (0,319). Consequently, in another word, the data normality level and the conclusion of the research show that; there is a significant relation between muscular leg power and 40 meter running speed with the result of triple jumping. The correlation is r= 0.878 where rcount > rtable or 0.942 > 0,319. The result also reveals that the relation can be categorized as a strong one. Hence, Ho is denied and Ha is accepted.Keywords: Muscular Leg Power, 40 Meter Running Speed And The Result Of Triple Jumping